Buying Butter and Guns - Oishee, Kundu (Cranfield University, 2020)
Is defence procurement different from other procurement activities of the government? This poster will present four cases of recent public procurement in the UK and compare the projects from their inception (tendering, selection of supplier) to final delivery in order to find the similarities and differences in military and civilian public procurement projects.It is easy to assume that defence is different or somehow ‘peculiar’ by claiming that the market is uncompetitive or that it is excessively political. However, there are rich literatures in management of major projects, innovation in large technical systems, and the economics of procurement in imperfect markets which suggest the potential for shared learning from seemingly unique projects in order to improve public procurement performance (i.e. to ensure projects are completed on-time and within budget).Methods and dataThe research project uses comparative case study to answer the research question and examines the procurement of the Queen Elizabeth class aircraft carriers, Ajax armoured fighting vehicle and the procurement of high-speed trains for the Thameslink and the Intercity Express Programme. Data is being obtained from government documents and reports (National Audit Office, Parliamentary Select Committees, government departments), Parliamentary debates, newspapers, trade press/industrial magazines, and interviews. The poster will present the data collected in a format that can easily inform the audience about the similarities and differences that can be observed between these four projects along three dimensions:(1) Competition: points related to the market structure, the level of competition between suppliers, and the selection of supplier(2) Challenges: technological, contractual, and political risks encountered in project delivery(3) Management and governance: scope and structure of project teams, training and capacity, turnover, performance review and accountabilityFindings and conclusionThe research uses multi-disciplinary perspectives (economics, management, public policy) for understanding procurement. The findings will be of interest to those interested in military procurement as well as those interested in the potential for cross-learning between the military and non-military sector on the topic of procuring large technical systems.Although data collection is underway and will be completed only by October, comparing the procurement of the Queen Elizabeth class aircraft carriers and rolling stock for the Thameslink programme already reveals important similarities in competition and challenges faced in the procurement of large technical systems by both the Ministry of Defence and the Department for Transport. Case study research is often criticized for not being generalizable but finding similarities in procurement experience for extremely complex projects (as the ones chosen) casts doubt on the assumption that defence procurement is different from civilian public procurement.
Keywords: 'Public procurement'; 'Defence procurement'; 'Public procurement and innovation'; 'DSDS19 Poster'; 'DSDS19'; 'Business and Management not elsewhere classified'; 'Economics'